2010
DOI: 10.4018/jictrda.2010010103
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Analyzing the Role of ICT on Agricultural Commercialization and Household Food Security

Abstract: Lack of agricultural information has been attributed to the inability of smallholder farmers to transition from subsistence to commercial agriculture. Recent efforts to improve smallholder access to agricultural information have seen increased application of ICT technologies in developing agriculture. These efforts use ICT-based market information to reduce transaction costs of smallholder participation in markets, promote commercialization, and improve household food security. Emerging studies document the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Recent literature documents the increased penetration of mobile phones in Africa (Okello, Al Hassan, & Okello, 2010;Kiiza, Mugisha, & Lwasa, 2010). Others studies have also found the use of ICT tools by traders in many developing countries (Jensen, 2007;Aker, 2008;De Silva, 2010).…”
Section: Types Of Ict Tools Used By Grain Traders In Kenyamentioning
confidence: 99%
“…Recent literature documents the increased penetration of mobile phones in Africa (Okello, Al Hassan, & Okello, 2010;Kiiza, Mugisha, & Lwasa, 2010). Others studies have also found the use of ICT tools by traders in many developing countries (Jensen, 2007;Aker, 2008;De Silva, 2010).…”
Section: Types Of Ict Tools Used By Grain Traders In Kenyamentioning
confidence: 99%
“…The use of ICT-enabled market information sources is associated with increased market transparency through the provision of current market information, while simultaneously improving incomes and leading to other welfare outcomes. However, the currently available studies have mostly examined how ICTs contribute to improving farmers' access to market information [3,4], their adoption of production technologies [5,6] or the associated livelihoods effects of its use [7]. Although some studies have explored the link between market information and commercialization, such as [8], the effect of adopting ICT-based information sources on market participation among smallholder livestock farmers in South Africa remains a grey area.…”
Section: Introductionmentioning
confidence: 99%
“…It is gaining wide acceptance as the new service delivery platform especially in developing countries. Mobile technology has been applied in healthcare (Anhoj & Moldrup, 2004;Miskelly, 2005;Kim and Jeong, 2007;Blake, 2008;Iluyemi, 2008Iluyemi, , 2009Lester et al, 2009;Blake, 2009); tourism (Cheverst et al, 2000;Brown & Chalmers, 2003;Fesenmaier et al, 2003;Brown et al, 2003;Schwinger et al, 2005;Kim et al, 2008); agriculture (de Silva & Ratnadiwakara, 2010; Maumbe & Okello, 2010;Okello et al, 2010;Katengeza et al, 2011;Lawal-Adebowale & Omotayo, 2012) and education (Lee et al, 2004;Naismith et al, 2004;Mostakhdemin-Hosseini & Tuimala, 2005;Laouris et al, 2005;Najafabadi, 2008).…”
Section: Introductionmentioning
confidence: 99%